Analisis Peran Advokat Dalam Menangani Perkara Perceraian - Nuri Luthfia; Fatimah Zahara; Siti Aminah (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This paper aims to analyze the analysis of the role of advocates in handling divorce cases. This paper is a literature study, in which researchers analyze various literature and articles, journals and books. The research results show that advocates are given freedom in carrying out their profession in addition to other rights granted by law, including the right to immunity, the right to obtain information regarding clients and the right to receive an honorarium. The existence of advocates to play a role in providing legal services to parties disputing in marriage, especially divorce which is regulated in Pasal 73 Ayat (1) Undang-Undang Nomor 7 Tahun 1989 Tentang Peradilan Agama. Mengacu pada undang undang nomor 18 tahun 2003. Keywords : Court, Advocate, Divorce